2023
DOI: 10.1021/jacs.2c13886
|View full text |Cite
|
Sign up to set email alerts
|

General Synthesis of a Diatomic Catalyst Library via a Macrocyclic Precursor-Mediated Approach

Abstract: Heterogeneous catalysts containing diatomic sites are often hypothesized to have distinctive reactivity due to synergistic effects, but there are limited approaches that enable the convenient production of diatomic catalysts (DACs) with diverse metal combinations. Here, we present a general synthetic strategy for constructing a DAC library across a wide spectrum of homonuclear (Fe 2 , Co 2 , Ni 2 , Cu 2 , Mn 2 , and Pd 2 ) and heteronuclear (Fe−Cu, Fe−Ni, Cu−Mn, and Cu−Co) bimetal centers. This strategy is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 52 publications
2
59
0
Order By: Relevance
“…The mechanical ball-milling and calcination treatment of porous material-encapsulated macrocyclic dual-metal complexes may be a promising general and largescale synthesis approach of DASCs. [47] Second, the characterization of atomic interactions in DASCs is still hard to achieve. Structural variables such as atomic size and local coordination environment make the characterization of DASCs more complex than that of the traditional metal catalysts in the form of single atoms, nanoclusters, and nanoparticles.…”
Section: Minireviewsmentioning
confidence: 99%
“…The mechanical ball-milling and calcination treatment of porous material-encapsulated macrocyclic dual-metal complexes may be a promising general and largescale synthesis approach of DASCs. [47] Second, the characterization of atomic interactions in DASCs is still hard to achieve. Structural variables such as atomic size and local coordination environment make the characterization of DASCs more complex than that of the traditional metal catalysts in the form of single atoms, nanoclusters, and nanoparticles.…”
Section: Minireviewsmentioning
confidence: 99%
“…Note that, in an experimental study, Chu et al 92 reported that the Fe−Ce DAC has a much higher ORR catalytic activity than Fe−N 4 , which agrees with the above calculations. Similarly, Co−Ni-1, 93 Fe−Ni-1, 94 Mn−Cu-0, 12 and Mn−Zn-0, 95 The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.jpcc.3c05753.…”
Section: Screening For Best-performing Catalysts the Mlpredicted Adso...mentioning
confidence: 99%
“…There has been abundant data in the ever‐evolving field of DACs. Pioneering works have already established standardized library of databases [28, 97] . These outstanding examples provide soild experimental database for the next generation of high‐throughput catalyst exploration and screening with ML and AI.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%